IMPLICATIONS OF KINESITHERAPY IN REGARD OF TREATING CHILDREN WITH HALLERMAN- STREIFF SYNDROME - Rabolu Elena (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The purpose of this paper is to underline once again kinesitherapy's role and importance in the recovery of children with serious motor, neuro-vegetative and joint disorders induced by chromosomal modifications. The actual research consisted of a sustained and guided kinetic program's application aiming to improve the quality of life in the patient with Hallermann -Streiff syndrome. The Portage assessment scale and the gross motor function measure were used to assess this program's effectiveness. Following the analysis of the final results, it can be firmly stated that when performed professionally, kinesitherapy can restore the child with Hallermann- Streiff syndrome the motor potential as close to his chronological age as possible by: toning-up the muscles and improving the articular mobility; restoring the kinestesic image of the motor area (command center for movements).